2019
DOI: 10.1371/journal.pone.0215455
|View full text |Cite
|
Sign up to set email alerts
|

Resilience, condom use self-efficacy, internalized homophobia, and condomless anal sex among black men who have sex with men, New York City

Abstract: Background Black men who have sex with men, who account for less than 1% of the U.S. population, account for approximately 25% of new HIV infections annually. Condomless anal sex contributes to HIV infection among black men who have sex with men. The capacity to recover quickly from difficulties (resilience) may be protective against condomless anal sex, but has been understudied among black men who have sex with men. Psychosocial factors related to resilience, i.e., condom use self-efficacy and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 34 publications
1
9
1
Order By: Relevance
“…Contrary to our hypothesis that IH will be positively associated with SRB, we did not find any direct effect of IH on SRB. Some studies found that higher levels of IH leads to SRB (Folch et al, 2009;Puckett et al, 2017), while some studies did not find evidence for this direct relationship (Dawson et al, 2019;Puckett et al, 2017), including ours. Therefore, our study further contributes to the literature which suggest that there might be potential mediating variables that affect the relation between IH and SRB (Kashubeck-West & Szymanski, 2008a;Newcomb & Mustanski, 2010b).…”
Section: Discussioncontrasting
confidence: 66%
“…Contrary to our hypothesis that IH will be positively associated with SRB, we did not find any direct effect of IH on SRB. Some studies found that higher levels of IH leads to SRB (Folch et al, 2009;Puckett et al, 2017), while some studies did not find evidence for this direct relationship (Dawson et al, 2019;Puckett et al, 2017), including ours. Therefore, our study further contributes to the literature which suggest that there might be potential mediating variables that affect the relation between IH and SRB (Kashubeck-West & Szymanski, 2008a;Newcomb & Mustanski, 2010b).…”
Section: Discussioncontrasting
confidence: 66%
“…They also suffer more adverse mental status (e.g., anxiety, low condom use self-efficacy) [15,54] and behavior (e.g., substance use) [20], increasing their condomless sex behavior. Besides, subgroup analysis suggested that the risk of condomless sex due to IH and the mediation and interaction effect of SC were only significant in the homosexual subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with previous studies. Dawson et al (2019) assessed the association between resilience, condom use self-efficacy, internalized homophobia, and unprotected anal sex among black men who have sex with men in New York City. The authors concluded that only increased levels of condom use self-efficacy were correlated with decreased unprotected anal sex.…”
Section: Discussionmentioning
confidence: 99%